(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
Troponins are proteins that are integral components of the contractile mechanism of muscle, including cardiac muscle. The measurement of cardiac troponins is used primarily to assist in the diagnosis or exclusion of myocardial injury. The article reports on the role of troponins in the laboratory diagnosis of myocardial infarction.